DEVELOPMENT OF INTERACTIVE ANIMATED VIDEO LEARNING MEDIA ON ENERGY TRANSFORMATION MATERIAL FOR CLASS IV PRIMARY SCHOOL - Afina, Nazzila Hasya; Irianto, Dede Margo; Aljamaliah, Syifa Nailul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research is based on the use of animated video learning media which has often been one-way between the media and students without actively involving students. This research was conducted to describe the initial design, results of design development, as well as user responses to interactive animated video learning media on energy transformation material. Interactive animated video learning media was developed using the Design and Development (D&D) research method and using the ADDIE research model which includes five stages, namely analysis, design, development, implementation, and evaluation. The results of the assessment of the interactive animated video learning media that have been developed are obtained from validation questionnaire scores by material experts of 88.89% in the